2018
DOI: 10.1088/1742-6596/1037/7/072010
|View full text |Cite
|
Sign up to set email alerts
|

Downstream effects from contemporary wind turbine deployments

Abstract: The Long distance wake behind Horns Rev I studied using large eddy simulations and a wind turbine parameterization in WRF O Eriksson, M Baltscheffsky, S-P Breton et al. Resulting analyses indicate that for both WT parameterizations impacts on temperature, specific humidity, precipitation, sensible and latent heat fluxes from current wind turbine deployments are statistically significant only in summer, are of very small magnitude, and are highly localized. It is also shown that use of the relatively recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Consistent with the summary above that compares the two wind farm parameterizations, prior research has also revealed important differences in wake profiles, downstream recovery and also gross capacity factors (CF) from the Fitch and EWP schemes (Pryor et al 2019;Volker et al 2015). For example, a numerical experiment describing the wind speed field inside and downwind of very large wind farms (10 5 km 2 ) with a WT spacing of 10.5D in three regions with distinct wind speed and roughness conditions showed wind speeds recovered to 2% above the maximum velocity deficit faster in EWP than Fitch (Volker et al 2017).…”
Section: Wind Farm Parameterizations In Wrfmentioning
confidence: 52%
See 3 more Smart Citations
“…Consistent with the summary above that compares the two wind farm parameterizations, prior research has also revealed important differences in wake profiles, downstream recovery and also gross capacity factors (CF) from the Fitch and EWP schemes (Pryor et al 2019;Volker et al 2015). For example, a numerical experiment describing the wind speed field inside and downwind of very large wind farms (10 5 km 2 ) with a WT spacing of 10.5D in three regions with distinct wind speed and roughness conditions showed wind speeds recovered to 2% above the maximum velocity deficit faster in EWP than Fitch (Volker et al 2017).…”
Section: Wind Farm Parameterizations In Wrfmentioning
confidence: 52%
“…The mean and 90th-percentile wind speeds are derived from each of the raw time series from d02_noWT for the three different resolutions. For visualization, the resulting monthly wind speed time series U from all grid cells in the subdomain centered over the Pomeroy cluster are also fitted to Weibull distributions using maximum likelihood methods to derive the distribution parameters (A and k, and confidence intervals thereon) (Pryor et al 2004;Wilks 2011):…”
Section: B Statistical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EWP approach shows a more linear reduction within the farm, while the Fitch approach shows a more exponential decrease. In addition, the maximum wind-speed deficit is simulated differently in the EWP and the Fitch parametrization with the EWP parametrization tending to show smaller wake effects (Volker et al 2015;Pryor et al 2018a;Shepherd et al 2020;Pryor et al 2020; not visible in Fig. 12).…”
Section: Impacts On Wind Speedmentioning
confidence: 99%